Accelerated dilution of liquefied natural gas plumes with fences and vortex generators: final report, August 1981-May 1982 - Meroney, Robert N., author; Kothari, K. M., author; Fluid Mechanics and Wind Engineering Program, Department of Civil Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1982)
A wind-tunnel test program was conducted on a 1:250 scale model to determine the effects of fences and vortex generators on the dispersion of LNG plumes. The tests were conducted simulating continuous LNG boil-off rates of 20, 30 and 40 m3/min; 4, 7, 9 and 12 m/sec wind speed for fence data and 4, 7 and 9 m/sec wind speed for vortex generator data; six configurations; and two heights of fences and vortex generators. Plots of ground-level mean concentration contours were constructed. The highest concentrations were observed for the case of no fences and vortex generators. Fences and vortex generators created higher turbulence intensity in the wake and resulted into enhanced mixing thus reducing the ground-level hazards of LNG plumes. In general, the lower wind speed gave the higher ground-level concentration when fence or vortex generator interacted with the LNG plume. However, for the case of no fence or vortex generator the higher concentration persisted for longer downwind distances for 7 m/sec wind speed. As expected, the ground-level concentrations were increased with an increase in LNG boil-off rate but decreased with the increase in the fence/vortex generator height. In general, the solid fences gave the lower ground-level concentration as compared with the vortex generator with identical conditions. The double fences or vortex generators gave the maximum LNG plume dilution. However, the single fence or vortex generator near the source gave approximately the same dilution and hence, it would not justify the additional expenses of having second fence or vortex generator. It was also observed that the maximum LNG plume dilution occurs when the fence or vortex generator is closest possible to the LNG spill area.
May 1982.
Report No. GRI-81/0074.
CER81-82KMK-RNM79.
Keywords: Wind tunnel models; Plumes (Fluid dynamics); Liquefied natural gas